A Fuzzy Logic Based Search Technique for Digital Libraries - Murty, S.G.K.; Biswas, R.N. (DESIDOC Journal of Library & Information Technology, 2003)
Conventional search techniques for searching a database follow Boolean logic. When a database search is made with a given set of keywords, a minor variation in the keyword due to difference in spelling standard, typographical error or difference in inflection of the same stem, results in failure in getting records from the database. This situation demands a special kind of search technique, which should take into account approximation along with exactness. Fuzzy sets are more appropriate to represent imprecise information and matching based on it is better suited to process it. As fuzzy logic is an extension of conventional logic; it handles the concept of partial truth along with true and false. Fuzzy logic more closely follows the way humans think and helps to handle real world complexities more efficiently. This paper presents a new information retrieval support technique used for database search, using fuzzy based matching and is expected to significantly enhance searching benefits over conventional approaches. http://dx.doi.org/10.14429/dbit.24.6.3640